Wooden "Air Purifiers" with Fire‐Retardancy and Smoke‐Suppression Properties. (1st November 2022) - Sun, Xiaohan; Yu, Qianqian; Yang, Zhaolin; Hu, Senwei; Yang, Haiyue; Wang, Xin; Zhou, Jiazuo; Yu, Yuan; Wang, Chengyu; Li, Yudong
Abstract: The demand for improved indoor air quality has grown with improvements in the standards of living worldwide. While wood is widely used to construct furniture since it is a renewable resource and aesthetically pleasing, it is also flammable, which limits its applications. Although there have been extensive research efforts in reducing the flammability of wood products, current approaches often have adverse effects on the environment. In this work, a novel organo‐inorganic coordination system is proposed to prepare a fire‐retardant and smoke suppression wooden "air purifier" using a vacuum impregnation method. The "air purifier" is composed of tourmaline particles/KH550 (TPs/KH550) and delignified wood. The added TPs give the final composites capable to purify air (1000 psc cm −3 negative oxygen ions [NOIs]). Compared with pristine wood (PW), total heat release (THR), peak heat release rate (HRR), and smoke production rate (SPR) of the wooden "air purifier" are reduced by 47.88%, 11.73%, and 82.81%, respectively, highlighting that the composites have good fire‐retardancy and smoke suppression performances. Life cycle assessment (LCA) results indicate the composites have minimal environmental impact (EI) in 15 categories. This green, eco‐friendly wooden "air purifier" with fire‐retardant and smoke suppression properties has a great potential application in furniture and buildings. Abstract : A novel organo‐inorganic coordination system is proposed to prepare a wooden "air purifier" with fire‐retardancy and smoke suppression properties, which is composed of tourmaline particles/KH550 and delignified wood by vacuum impregnation method. Life cycle assessment is used to initially evaluate fire retardant methods of wood, which demonstrates that this work is an eco‐friendly method to prepare fire retardant wood.